"Physician's prescriptions accurately prepared" - The Mid-Nineteenth-Century Prescription Books of Four Gloucester Chemists. (22nd May 2020) - Helm, David P
Abstract: Britain's mid-nineteenth-century healthcare economy has often been described as a "medical marketplace" in which struggling doctors faced intense competition from a range of unqualified rivals. Chemists and druggists, who proliferated in industrial cities and supposedly prospered by exploiting the poor and the gullible, are widely regarded as having presented a serious threat to medical livelihoods. However, the activities of four Gloucester chemists show how the dispensing of medical prescriptions brought individual chemists and doctors closer together. Competition between chemists and druggists for this trade was intense and it was instrumental in establishing them as trusted community pharmacists and giving impetus to the process of professionalization. Prescription books, an under-represented source in the literature, also show that customers for prescription medicines were surprisingly socially diverse and that most prescriptions were collected by women, with significant variation in dispensing activity through the week. This, and the volume of prescriptions being dispensed, suggest prescription medicines were regularly being used to treat chronic and less serious ailments, where collection could await normal shopping days. Significantly, prescriptions were the property of the patients and could be re-presented whenever they thought fit. For some patients, it thus effectively became an instrument of self-medication.